The Expressive Discourse in Contemporary Arab Ceramics, Nasser Halabi as a Model - Dana salahaddin shareef (Zanco Journal of Human Sciences, 2025)
The Expressive Discourse in Contemporary Arab Ceramics, Nasser Halabi as a Model The plastic art in all its specializations works within an influential discursive scene in the artistic work within the elements and foundations of formation that organize the work, its creation and its exit carry within it a certain content and a certain regulatory body. In order for the artwork to have an aesthetic effect, and among the plastic structures, the expressive discourse and the sense of it stand out. Expressive discourse occupied an important concept in the process of constructing the artwork. Expressive discourse was an important act to achieve the saving intellectual visions in the artwork in order to give different visual and aesthetic sensations in the art of cer From here the current research came to study the expressive discoursethe ceramic scene of the works of the potter Nasser Halabi, where the research problem started from a sentence, I ask him that ended in the following question